TAM Construct, Trust, and Religiosity for Decision of Muslim Lenders to Use Funding Services on Sharia Peer-to-Peer Lending Platforms (Website and Apps) - Muhammad Aladdin Hanif; Purbayu Budi Santosa (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT The study aims to analyze the factors that influence the decision of a Muslim lender to use funding services on Islamic peer to peer lending platform. The data analysis method used in this study is binary logistic regression analysis using the analysis tool of IBM SPSS Statistics 26 software. Populations in this study are Muslim communities who have used or are using funding services on peer to peer lending platforms in Indonesia (lender muslim). Sampling is based on the nonprobability sampling technique. Collecting research data through the process of distributing questionnaires to 330 respondents. The research findings indicate that Muslim lenders who make decisions to use financing services on Islamic peer to peer lending platforms are influenced by perceived ease of use, perceived usefulness, perceived risk, and religiosity. Trust has no influence on the decision of the Muslim lender to use the financing services on Islamic peer to peer lending platform. The main construction of the Technology Acceptance Model has a strong influence on the context of this research. The implications of the findings of this study are expected to contribute to sharia peer to peer lending fintech companies in designing effective strategies to increase the number of lenders in sharia peer to peer fintech lending, especially Muslim lenders. Keywords: Consumer behavior, technology acceptance, decision to use, Islamic peer to peer lending.   ABSTRAK Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi keputusan lender muslim dalam menggunakan layanan pendanaan di platform peer to peer lending syariah. Metode analisis data yang digunakan pada penelitian ini adalah analisis regresi logistik biner dengan menggunakan alat analisis berupa software IBM SPSS Statistics 26. Populasi pada penelitian ini adalah masyarakat muslim yang pernah atau sedang menggunakan layanan pendanaan di platform peer to peer lending syariah atau konvensional di Indonesia (lender muslim). Pemilihan sampel menggunakan teknik nonprobability sampling, yaitu purposive sampling. Pengumpulan data penelitian melalui proses penyebaran kuesioner kepada 330 responden. Temuan penelitian mengindikasikan bahwa lender muslim yang membuat keputusan penggunaan layanan pendanaan di platform peer to peer lending syariah dipengaruhi oleh persepsi kemudahan penggunaan, persepsi kegunaan, persepsi risiko, dan religiusitas. Kepercayaan tidak memiliki pengaruh terhadap keputusan lender muslim dalam menggunakan dalam layanan pendanaan di platform peer to peer lending syariah. Konstruk utama Technology Acceptance Model memiliki pengaruh yang kuat pada konteks penelitian ini. Implikasi dari temuan penelitian ini diharapkan dapat memberikan kontribusi terhadap perusahaan fintech peer to peer lending syariah dalam merancang strategi yang efektif untuk meningkatkan jumlah lender pada fintech peer to peer lending syariah khususnya lender muslim. Kata Kunci: Perilaku konsumen, penerimaan teknologi, keputusan penggunaan, peer to peer lending syariah.